Prevalence and factors associated with underweight children: a population-based subnational analysis from Pakistan - Ramesh Kumar; Faisal Abbas; Ratana Somrongthong (BMJ Open)
Objectives This study aims to determine the prevalence of and factors associated with underweight children under the age of 5 in Punjab, Pakistan.Design We analysed cross-sectional household-level subnationally representative Multiple Indicator Cluster Survey.Settings Punjab province, Pakistan.Participants 24 042 children under 5 years of age.Data analysis Multilevel multivariate logistic regression analysis.Results Prevalence of moderately and severely underweight children was found to be (33.3% and 11.3%, respectively). Multivariate multilevel logistic regression results show that as the child grows older the likelihood of the child being underweight increases significantly (eg, children between 12 and 23 months are one and half times more likely to be underweight, whereas children between the ages of 36 and 47 months are two and a half times more likely to be underweight). Gender was found to be another significant factor contributing to underweight prevalence among children under the age of 5. The likelihood of a girl child being underweight is more than that of a boy child being underweight (OR 0.92, 95% CI 0.8 to 1.0). Similarly, a child whose birth order is three or more is two times more likely to be underweight (OR 1.96, 95% CI 1.5 to 2.5) relative to a child of a lower birth order. Moreover, diarrhoea also significantly increases the likelihood of the child being underweight (OR 1.31, 95% CI 1.1 to 1.5). Child size is another determinant for underweight prevalence among children under 5, for example, a child with a size smaller than average at the time of birth is 2.7 times more likely to be moderately underweight than a child with an average or larger than average size at the time of birth.Conclusion Rigorous community-based interventions should be developed and executed throughout the province to improve this grave situation of underweight prevalence in Punjab. Mother’s education should be uplifted by providing them formal education and providing awareness about the importance of proper nutrition for children.